Detection of damaged supports under railway track based on frequency shift. (31st March 2017) - Wang, Longqi; Zhang, Yao; Lie, Seng Tjhen
Abstract: In railway transportation systems, the tracks are usually fastened on sleepers which are supported by the ballast. A lot of research has been conducted to guarantee the safety of railway track because of its importance, and more concern is expressed about monitoring of track itself such as railway level and alignment. The ballast and fasteners which provide strong support to the railway track are important as well whereas the detection of loose or missing fasteners and damaged ballast mainly relies on visual inspection. Although it is reliable when the fastener is missing and the damaged ballast is on the surface, it provides less help if the fastener is only loose and the damaged ballast is under the sleepers, which are however frequently observed in practice. This paper proposes an approach based on frequency shift to identify the damaged supports including the loose or missing fasteners and damaged ballast. In this study, the rail-sleeper-ballast system is modeled as an Euler beam evenly supported by a series of springs, the stiffness of which are reduced when the fastener is loose or missing and the ballast under the sleepers is damaged. An auxiliary mass is utilized herein and when it is mounted on the beam, the natural frequencies of the whole system will change with respect to the location of the auxiliary mass. The auxiliary mass induced frequency shift is analyzed and it is found the natural frequencies change periodically when the supports are undamaged, whereas the periodicity will be broken due to damaged supports. In fact, the natural frequencies drop clearly when the auxiliary mass moves over the damaged support. A special damage index only using the information of the damaged states is proposed and both numerical and experimental examples are carried out to validate the proposed method.